708 Rapid Adoption of Telemedicine during COVID-19 Pandemic: Impact on PAP Adherence and Health Care Utilization. (3rd May 2021) - Stothard, Ellen; Hickey, Mark; McCarty, David; Wertz, Adam
Abstract: Introduction: The COVID-19 pandemic has required rapid reconfiguration of healthcare services from in-person to telemedicine. Positive Airway Pressure (PAP) is the gold-standard treatment for sleep apnea, but success requires substantial clinical support, which has traditionally been provided in-person. In this quality analysis, we examined the impact of PAP initiation (PAPI) via telemedicine on adherence and subsequent health care utilization, compared to the conventional, in-person model. Methods: Patients who completed PAPI and initial adherence period between April-August 2020 were included. During this window, telemedicine visits were encouraged, but not required. Adequate adherence status was considered met if 21/30 consecutive days with use >4h was achieved by day 90 therapy. Health care utilization was represented by the number of follow-up visits, stratified by provider type (Physician, Physician Assistant (PA), or PAP Technologist). Results: 839 patients (54% telemedicine, 46% in-person), 38.0% female, aged 54.2±0.5 years, BMI 32.4±0.3 (±SEM) were included. Adherence was similarly achieved following both initiation methods: 78.8% (telemedicine) and 76.4% (in-person) (p>0.4). Clinical follow-up was lower after in-person PAPI compared to telemedicine, regardless of adherence status (p<0.05). Non-adherent patients also had less clinical follow-up than adherent patients after both initiation methods (p<0.0001), though this differed by provider type. Non-adherent patients in both initiation methods were less likely to follow-up with a PA or PAP Technologist (p<0.01), though follow-up rate with Physician providers was similar (p>0.1). Clinical follow-up with PAP Technologist was increased after telemedicine compared to in-person PAPI (p<0.01). Conclusion: Implementation of a telemedicine PAP initiation protocol during the COVID-19 pandemic resulted in similar rates of adherence compared to the conventional in-person method, which suggests that telemedicine is an appropriate alternative to in-person PAPI. However, clinical follow-up was lower after in-person PAPI compared to telemedicine regardless of adherence status. Further, non-adherent patients had less follow-up with PAs and PAP Technologists, but similar follow-up with Physicians. This may indicate that provider type plays a role in supporting patients through the adherence process and should be considered. Further research is needed to understand the relationship between care teams, adherence, and healthcare utilization in the age of telemedicine. Support (if any):